Separability, Competence-Competence and the Arbitrator’s Jurisdiction in Singapore - LEE, Jack Tsen-Ta (Institutional Knowledge at Singapore Management University, 1995)
The concepts of separability and competence-competence, which promote arbitral autonomy, exist in many jurisdictions. This article surveys the extent of their acceptance in Singapore's domestic and international arbitration law, and suggests that legislative refinements are necessary to remove doubts and resolve conflicts between the law and the SIAC [Singapore International Arbitration Centre] Rules.